Salso-Sulphide Thermal Water in the Prevention of Recurrent Respiratory Infections in Children. (October 2013) - Varricchio, A.; Giuliano, M.; Capasso, M.; Del Gaizo, D.; Ascione, E.; De Lucia, A.; Avvisati, F.; Capuano, F.; De Rosa, G.; Di Mauro, F.; Ciprandi, G.
Recurrent respiratory infections (RRI) represent a social problem for both the pharmaco-economic impact and the burden on the family. Thermal water is popularly well accepted. However, there is no scientific evidence of its preventive activity on recurrent respiratory tract infections (RRI). Therefore, the purpose of this study was to evaluate the effects of Agnano thermal water nasal irrigation on RRI prevention in children. A total of 107 children (70 males, mean age 4.5±1.2 years) with RRI were enrolled in the study. At baseline, children were randomly assigned to the treatment with: A) inhaled crenotherapy with salso-sulphide water or B) isotonic saline (NaCl 0.9%). Inhaled therapy was performed using nasal washing by Rino-jet (ASEMA srl, Milan, Italy) b.i.d. for 12 days. Nasal washing lasted 2 minutes per nostril. Immediately before washing, children inhaled 1 l of water by stream inhalation per 2 minutes. Crenotherapy was capable of significantly reducing: the number of respiratory infections, nasal symptoms, neutrophil and bacteria count, turbinate and adenoidal hypertrophy, presence of biofilm, and blockage of ostiomeatal complex (OCM). In conclusion, this study provides the first evidence that Agnano crenotherapy may be capable of preventing RRI in children as it exerts some positive effects, such as reduction of nasal obstruction, OCM blockage, biofilm, and inflammatory events.